Rancang Bangun Aplikasi Disposisi Persuratan Berbasis Mobile Apps - Farida Yusuf; Asrul Azhari Muin; Nisrawati Nisrawati (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2022)
Letter disposition is a response that a document received and read by work supervisor/leader as follow-up activity. Next step is to instruct the subordinate to finish remaining tasks flow. The process of this letter disposition is one of the activities at the Makassar City DPRD office which is still less effective processes. One obstacle in the disposition process is need more time to be completed, where the work supervisor is not always in place caused by bustle. Consequently affected to the distribution process of letters. This study aims to determine the implementation of the letter disposition system that occurs at the Makassar City DPRD office and then attempt a solution to a system to facilitate staff or employees in managing letters. This research is a type of qualitative research with data collection techniques used, namely by observation, interviews and documentation review. Then the data obtained were analyzed descriptively qualitatively. The resulting system includes several features such as incoming and outgoing mail data, disposition processes, employee users, and reporting.